The Relations Between the People of Hills and Plains in the pre-colonial period of Assam with special reference to the Posa system of the Ahom administration - Kaur, Dr. Harpinder (The journal of contemporary issues in business and government, 2019)
In the pre-colonial period of Assam, Assam was specially ruled by the Ahom rulers. The Ahom rulers during their long lasted regime of 600 years generally followed an unique policy of conciliation towards the hill tribes. The kingdom of Assam was bounded on the northeast and south by hills inhabited by various tribes, each with its distinctive manners. Customs and languages. As the tracts inhabited by the hill tribes did not yield well enough to meet their requirements, they used to make inroads into the fertile foothill plains inside the Ahom territories and sometimes forced the plain people to give their produce and services to them. The Ahoms, on their part, usually avoided retaliatory expeditions against these tribes, which were not only expensive but unpredictably hazardous. Of course, in order to put a stop to the inroads of the hill people to the bordering territories the Ahom Government either gave them fertile lands at the foot of their hills called khats along with access to certain fisheries in the plains or the payment of a stipulated amount called posa consisting of such articls as rice, cloth, cattle etc to be collected from a class of paiks called bahatiyas assigned to them or the privilege of having commercial transactions with the plains. In return for this, they were to acknowledge the suzerainty of the Ahom King and pay him ans annual tribute consisting of the articles produced in their respective hill areas.